The epidemiology of bacterial pneumonia in Black Bengal goats in Bangladesh (Bangladesh Veterinarian, 2016)
Goat pneumonia is commonly caused by infectious agents. The present study was conducted at Mymensingh Sadar (District headquarters) and Ullahpara Upazillas (Subdistrict). In each area goats with a history of pneumonia were identified. Age, sex, season, health status and hygienic practices of the affected flocks were recorded. Lungs and nasal swabs were collected from 250 Black Bengal goats for bacteriological examination. The prevalence of pneumonia was higher in young goats (1-12 months old) than in adults (>12 to 36 months old) (33% and 11.3%, respectively) (P